Peran Guru PAI dalam Membentuk Karakter Melalui Program Sekolah Ramah Anak (SRA) di SMPN 7 Yogyakarta - Muhammad Ilham (Lembaga Sosial Rumah Indonesia, 2021)
The background of this research is that the teacher of Islamic Religious Education is one of the elements that influence the process of character building at SMPN 7 Yogyakarta. Through the Child-Friendly School program, the process of character building becomes more positive for the development of students. The purpose of this study is to describe the role of PAI teachers and analyze the results achieved by PAI teachers in shaping the character of students through the Child-Friendly School (SRA) program at SMPN 7 Yogyakarta. This research is descriptive qualitative research. The results of this study are that in the process of character building the Islamic Religious Education teacher acts as an educator, leader, uswatun hasanah to shape the character of students in school to make a generation who is tough, has a noble character, is tolerant, and has a Muslim personality. With a persuasive approach by Islamic Religious Education Teachers can shape the learning culture in schools to be hospitable.